2023
DOI: 10.5937/fme2304606s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3/CuO hybrid nanoparticles dispersion on melting process of PCM in a triplex tube heat storage

Ibrahim Sadiq,
Sattar Aljabai,
Abdulhassan Karamallah

Abstract: This research conducts an experimental and theoretical investigation of the melting characteristics of a phase change material in a triplex tube heat storage. A three-dimensional model is simulated numerically employing Ansys Fluent software. The enthalpy porosity method is chosen for solving the phase transition of paraffin wax. A blend of equal-volume CuO and Al2O3 hybrid nano-additives was used as conductive material to enhance heat transfer in PCM, which can be considered the originality of this study. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…They found that the magnetic field's effect is insignificant at the beginning of the charging process, but it becomes increasingly considerable as time progresses. Sadiq et al [29] carried out an experimental and numerical study to discover the thermal performance of a triplex tube heat storage by inserting paraffin wax on the annulus side. A blend of Al2O3 and CuO was used as conductive particle to enhance the thermal characteristics of Paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the magnetic field's effect is insignificant at the beginning of the charging process, but it becomes increasingly considerable as time progresses. Sadiq et al [29] carried out an experimental and numerical study to discover the thermal performance of a triplex tube heat storage by inserting paraffin wax on the annulus side. A blend of Al2O3 and CuO was used as conductive particle to enhance the thermal characteristics of Paraffin.…”
Section: Introductionmentioning
confidence: 99%